You read to me, I'll read to you : very short fables to read together - Hoberman, Mary Ann (Hoberman, Mary Ann. You read to me, I'll read to you., 2010)
Retells thirteen of Aesop's fables, with each short poem inviting two readers to read their own parts, and then read the passage in the central column together.